Digital Collection Transformation At The Library of National Cheng Kung University Taiwan: An Evaluation - Fridayani, Helen Dian; Iqbal, Muhammad (Indonesian Journal of Librarianship, 2022)
Abstract Background: This paper evaluates digital collections and investigates digital collection transformation at National Cheng Kung University's Central Library in Taiwan. The NCKU case study highlights some issues that must be addressed, such as analyzing user information, improving library capacity and skills, developing digital resources, funding IT infrastructure development, and long-term database development for E-learning. Purpose: The goal of this study is to assess the readiness of the library collection center's planning for digital transformation, from the user perspective, students in particularly. Method: qualitative descriptive research method and supported by survey data conducted by NCKU. Result: The findings indicate that users are ready for the library collection center's digital transformation. However, the digital library collection center necessitates more careful planning, particularly in terms of socialization. Conclusion: Digital library's rich digital information and digital learning materials enable users to study and research at any time and from any location, in the format of lifelong learning and personalized learning. Libraries are considered the heart of any higher education institution and play a significant role. Keywords: Digital, Library, Acceptance of Technology, Transformation